The interplay between acute bacterial skin and skin structure infections and depression: a vicious circle of major clinical importance. Issue 2 (April 2020) - Bassetti, Matteo; Almirante, Benito; Giamarellos-Bourboulis, Evangelos J.; Gournellis, Rossetos; Grande, Iria; Marini, Maria Giulia; Balestrieri, Matteo
Abstract : Purpose of review: Previous studies suggest an association between depression and increased risk of various type of infections, including acute bacterial skin and skin structure infections (ABSSSI). Here, we review the latest advancement in our understanding of immunity in patients with depression and its relevance to disease management and diagnosis, with a special focus on patients suffering from ABSSSI. Recent findings: Recent studies have highlighted the role of hypothalamic–pituitary–adrenal axis, neuro-endocrine stress signaling pathways and behavioral attitudes (substance abuse and homelessness) in the pathogenesis of infections in depressed patients. Furthermore, acute bacterial infections, in turn, have emerged as a possible risk for depression development because of different mechanisms including antibiotic-driven changes in the microbiota. Summary: Recent evidences have emphasized the threat that comanagement of depression and infection pose to infectious disease physician and psychiatrist. Depressed patients with ABSSSI must be closely monitored for drug side-effects, drug–drug interactions, toxicity, and adequate compliance. New management strategies including new long-acting antibiotics (e.g., dalbavancin) are welcome.